(untitled) (gjstudies, 2016)
This research examines the critical role of Information Systems auditors inenhancing compliance with Sarbanes-Oxley Act (SOX) Section 404 and FederalFinancial Institutions Examination Council (FFIEC) guidelines within the banking sector. Through comprehensive analysis of 320 compliance audits across 65U.S. banking institutions from 2012-2015, this study develops a multidimensionalframework for evaluating IT control effectiveness under regulatory standards. Thefindings demonstrate that organizations with integrated IS audit functions achieve42% higher compliance rates with SOX Section 404 requirements and 58% fasterremediation of FFIEC-identified control deficiencies. The research introduces theRegulatory Compliance Maturity Model (RCMM), which identifies five critical dimensions influencing audit effectiveness: control environment assessment, documentation rigor, testing methodology, deficiency management, and continuous monitoring. Statistical analysis reveals strong correlation (r=0.81, p¡0.001) between RCMMscores and regulatory examination outcomes. Banks with mature IS audit capabilities experienced 67% fewer material weaknesses in internal controls and reducedcompliance-related costs by 31% through optimized audit processes. These findings underscore the strategic value of IS auditors in navigating complex regulatorylandscapes and provide practical frameworks for enhancing compliance effectivenesswhile reducing associated burdens.